Personal factors of pedagogy stundents that influence their social, ethical and legal formation regarding ICT - Flores-Lueg, Carolina; Roig-Vila, Rosabel (Revista Hipótese, 2017)
The pervasiveness of Information Technologies and Communication in the different social fields has generated new scenarios of communication, interaction, access to information and new forms of citizen participation. Against this, the teachers today must be prepared to offer alternatives that promote good practices of the learners when facing ICT aspect to be considered from the initial teacher training. This research was conducted at a Chilean university under a descriptive and correlational design. 175 students of Pedagogy a scale designed ad hoc for the study was applied in order to detect those personal factors that have an impact on self-perceived levels of performance in the dimension Social, Ethical and Legal Aspects of digital competence. Sex, educational level of initial training and attitude are the variables that showed statistical significance.
Keywords: University; Teacher education; Citizen participation